Monitoring and Promoting Physical Activity, Physical Fitness and Motor Competence in Children - Georgian, Badicu; Silva, Ana Filipa; Borges Sarmento, Hugo Miguel (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
As we know, a large amount of research confirms that physical activity (PA), physical fitness (PF), and motor competence (MC) are associated with health benefits in individuals of all ages. Achieving a sufficient level of PA and PF will consequently further contribute to better health-related biomarkers. Moreover, holding a good MC allows better participation in PA and exercise in life, promoting greater physical literacy.It is true that the measurement of PA in children and young people is subject to several conditioning factors which threaten validity and reliability. Additionally, it is good to remember that the World Health Organization guidelines on PA and sedentary behaviour for children recommend: (1) 180 min of PA (at any intensity) for two-year old children; (2) 180 min of PA, of which 60 min is moderate-to-vigorous physical activity (MVPA), for 3- to 4-year-old children; and (3) at least 60 min of MVPA for children and adolescents from 5 to 17 years old.Therefore, understanding and developing strategies to promote PA behavior is now more important than in the past, because it is essential to improve fitness levels and MC in early ages. These strategies should cover all generations, children and youth, adults and the elderly, equally, because negative outcomes are visible in individuals of all ages.In this Special Issue, we show contributions that describe and list the link, monitoring and promotion between PA, PF, and MC.